Paradigm of Family and Community Resilience in the Context of Ideology and Education during the Covid 19 Pandemic - Harta, Lilik Indri; Budiman, Lestanta; Rahatmawati, Istiana; Hastangka, Hastangka (RSF Conference Series: Business, Management and Social Sciences, 2021)
The Covid-19 pandemic has severely hit the world since 2020 to this day, significantly impacting the life of communities and nation. Such significant impacts can be seen from two main aspects, namely direct and indirect ones. Direct impacts can be identified from economy and healthcare quality. In terms of economic impacts, the pandemic has caused more people to be into economic distress and economic uncertainty, unemployment to rise, and many to lose a decent everyday life. In terms of impact on healthcare, many have a great difficulty accessing a good healthcare quality and the healthcare quality has decreased in times of the Covid-19 pandemic. Meanwhile, the indirect impact can be seen from multiple conditions, starting from education, social issue, ideology, politics, and security. This research focused on the efforts to build family and community resilience amidst the pandemic while radicalism, fundamentalism, and terrorism are still an issue. The aim of this paper was to describe and offer a paradigm of family and community resilience as an effort to reinforce Pancasila ideology in times of the Covid-19 pandemic. The method employed for this research was a qualitative approach through literature studies and empirical research or observation, and hence the analysis used was interpretation and critical discourse analysis. A limitation of this research was only focusing on Pancasila as well as family and society resilience during Covid-19. The result of this study expectedly can be a clear recommendation to family and community resilience paradigm.